Disability-adjusted life years for colorectal cancer in China, 2017–2030: A prevalence-based analysis focusing on the impact of screening coverage and the application of local weights - Yujie Wu; Yanjie Li; Xin Wang; Xinyi Zhou; Xinxin Yan; Hong Wang; Juan Zhu; Wanqing Chen; Jufang Shi; Jinjiao Li (Chinese Medical Journal)
Abstract. Background:. Most studies have evaluated disability-adjusted life years (DALYs) of colorectal cancer (CRC) patients based on a set of generic disability weights (DWs). This study aimed to apply local CRC-stage-specific DWs to estimate the burden of DALYs for CRC (CRC-DALYs) in populations in China and consider the influence of local screening coverage of CRC. Methods:. A prevalence-based model was constructed using data from various sources. Years lived with disability (YLDs) were estimated mainly via cumulative prevalence data (based on CRC incidence rates, population numbers, and survival rates), stage-specific proportions of CRC, and DWs of the local population. Years of life lost (YLLs) were calculated based on the CRC mortality rates and standard life expectancies. CRC incidence and mortality rates for the years 2020, 2025, and 2030 were estimated by joinpoint regression, and the corresponding DALYs were predicted. The main assumption was made for CRC screening coverage. Sensitivity analyses were used to assess the impact of population, DWs, and coverage. Results:. In 2017, among the Chinese population, the estimated number of CRC-DALYs was 4,303,314 (11.9% for YLDs). If CRC screening coverage rate in China (2.3%) remains unchanged, the overall DALYs in 2030 are predicted to increase by 37.2% (45.1% of those aged ≥65 years). More optimistically, the DALYs would then decrease by 0.7% in 2030 (from 5,902,454 to 5,860,200) if the coverage could be increased to 25.0%. A sensitivity analysis revealed that using local DWs would change the base-case values by 5.7%. Conclusions:. The estimated CRC-DALYs in China using population-specific DWs were considerably lower (with a higher percentage of YLDs) than the global burden of disease (GBD) estimates (5,865,004, of 4.6% for YLDs), suggesting the impact extent of applying local parameters. Sustainable scale-up CRC screening needs to be in place to moderate the growth trend of CRC-DALYs in China.